An empirical study on critical successfull factors of information and communication technology (ICT) usage in successful private organizations in Kuching - Moh, Ung Kieng (Universiti Malaysia Sarawak (UNIMAS), 2003)
This study is to determine the CSFs that influence ICT usage among the successful private sectors across various industries in Kuching. Since government of Sarawak vigorously promotes ICT usage, it is interesting to investigate the salient factors that determine the extent usage of ICT among successful private organizations. Some organizations may be very successful without extensive ICT usage